INDUKSI MUTASI PADA PISANG (Musa sp. - ABB) cv. KEPOK DENGAN IRADIASI GAMMA SECARA IN VITRO - Masykuroh, Luthfia; Adisyahputra, Adisyahputra; Indrayanti, Reni (Bioma, 2016)
Banana (Musa sp. - ABB) cv. Kepok is one of type banana processed that have a very potential commodities fruit developed to support food survival. The purpose of this study was to knowing the effect of gamma irradiation on the growth of banana plants cv. Kepok in vitro. This study was conducted in October 2014 – October 2015 in Plant Tissue Culture Laboratory, Biological – Science UNJ. The methods used was experiment with fully randomized design. Factors that tested was 6 gamma irradiation doses (0, 20, 30, 40, 50, 60 Gy) with 10 repetition. Observation of phenotypic generate diverse characters on the growth of the number of shoots and leaves. Gamma irradiation dose of 50 Gy is doses most inhibits the growth of character. Mutations that occur in banana plantlets cv. Kepok generated by the treatment doses gamma irradiation induced mutation is random.